Digital Accountability in Collaborative Public Governance in Times of Crisis: Analysing the Debate in a Polarized Social Forum. - Polzer, Tobias; Öner, Selin (Abacus, 2025)
Accountability in collaborative public governance initiatives and in digital era governance is under‐researched, especially in the context of crisis and where issues are debated in a social forum. Accountability considerations are considered particularly important in collaborative governance arrangements, which are of growing relevance for delivering public services. This study, anchored in notions of digital accountability, analyzes debate in a social media forum about a collaborative governance initiative implemented during a crisis. The empirical case is the Austrian contact tracing app, a digital innovation considered key in managing the COVID‐19 pandemic. The study makes several contributions. First, it is one of the first to focus on the crucial role of debate in digital accountability in collaborative governance. Second, the study shows that the debate extends beyond the mere content of the innovation, highlighting the need to consider the 'ecology' of other (digital) tools, measures, and policies for crisis mitigation in parallel. Third, the study sheds light on the temporal dynamics of accountability in crisis response. The study contributes conceptually to an enhanced understanding of the expertise of actors in delivering and receiving digital public services. It also contributes to a management perspective of digital accountability, which is important given the potential implications for (non)acceptance of public sector innovations in crises and beyond. An enhanced understanding is possibly even more crucial for innovations requiring citizen co‐production in sensitive areas such as health.